Nursing care for drug-dependent teenagers living on the streets (Research, Society and Development, 2023)
The main focus of the following work is nursing care for drug-dependent teenagers living on the streets, with the aim of revealing reality and the active search for a better solution to this public health problem. It is necessary to discuss and analyze the factors that help the persistence of this bias, through bibliographical research of an integrative and qualitative nature of the literature, whose purpose is to provide better nursing care for the appropriate group and, to reiterate, the real appreciation of the professional in tackling the problem in question. It is noteworthy that nursing graduation is successful in training more qualified professionals in terms of monitoring, treating and welcoming drug-dependent homeless adolescents, in order to build nursing that is increasingly more humane and capable of providing time and voice to this population, still so stigmatized in Brazil. Therefore, the technical-scientific knowledge of academics and nursing professionals in this social context is of utmost importance, acting in a multidisciplinary way and carrying out work in the biopsychosocial sphere, with the support of health strategies so that there is greater attention focused on this population neglected.